1993
DOI: 10.1021/jm00077a005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and neutrophil-inhibiting properties of new 2-O-methyl-6-(alkylthio)ascorbic acid derivatives

Abstract: A series of new 6-(alkylthio)ascorbic acids was synthesized, and their inhibitory effects on lipid peroxidation and the oxidative burst of human neutrophils were tested. Of 12 structurally different lipophilic ascorbic acid derivatives 6-S-n-hexadecyl-2-O-methyl-6-deoxy-6-thio-L-ascorbic acid (7b; B-003) inhibited the Fe2+/ADP-induced lipid peroxidation of rat liver microsomes with an IC50 value of 2 microM. In human neutrophils, 7b most potently inhibited the fMLP-induced oxidative burst in a cell density-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The autooxidation of Fe 2 aADPaascorbate causes massive lipid peroxidation in liver microsomes, and this can be monitored by the generation of malondialdehyde. When investigating the effects of the new ascorbic acid derivatives (series 3 and 5) on lipid peroxidation, compound 5f was found to signi®cantly reduce malondialdehyde production with an IC50 value of 4Á85 6 10 À4 M. Similarly, Schmid et al (1993) reported the synthesis of 2-Omethyl-6-(alkylthio)ascorbic acid derivatives, one of which (6-S-n-hexadecylthio derivative) inhibited the Fe 2 aADPaascorbate-induced lipid peroxidation of rat liver microsomes with an IC50 value of 2 mM. The results of the lipid-peroxidation assay con®rm the good activity of compound 5f in the test for reducing activity of DPPH.…”
Section: Compoundmentioning
confidence: 99%
“…The autooxidation of Fe 2 aADPaascorbate causes massive lipid peroxidation in liver microsomes, and this can be monitored by the generation of malondialdehyde. When investigating the effects of the new ascorbic acid derivatives (series 3 and 5) on lipid peroxidation, compound 5f was found to signi®cantly reduce malondialdehyde production with an IC50 value of 4Á85 6 10 À4 M. Similarly, Schmid et al (1993) reported the synthesis of 2-Omethyl-6-(alkylthio)ascorbic acid derivatives, one of which (6-S-n-hexadecylthio derivative) inhibited the Fe 2 aADPaascorbate-induced lipid peroxidation of rat liver microsomes with an IC50 value of 2 mM. The results of the lipid-peroxidation assay con®rm the good activity of compound 5f in the test for reducing activity of DPPH.…”
Section: Compoundmentioning
confidence: 99%
“…It is well documented that uncontrolled release of ROS during inflammation may lead to severe tissue damage. Hence, considerable interest is directed towards developing agents capable of blocking the destructive effect of reactive oxidants in inflammatory conditions [Schmid et al, 1993;Kettle et al, 1993]. Antioxidants, e.g., low molecular weight thiols, have been applied to diminish damage caused by oxidative stress; thus, they have been used as antidotes in conditions such as paracetamol-intoxication [Prescott et al, 1976;Kourounakis et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…This protection is based on the production of oxidative bursts [9] at the site of microbial invasion, and the mechanisms of the site-directed killing of microorganisms and tumorous and virus-infected cells have been extensively studied [10]. On the other hand, the uncontrolled release of reactive oxygen species (ROS) is…”
mentioning
confidence: 99%